Long-distance wind-borne dispersal of the moth Cornifrons ulceratalis (Lepidoptera: Crambidae: Evergestinae) into the northern Mediterranean - Jordi DANTART; Constantí STEFANESCU; Anna ÀVILA; Marta ALARCÓN (European Journal of Entomology, 2009)
On October 2006, during an episode of abnormally warm weather, the African moth Cornifrons ulceratalis (Lederer, 1858) was captured simultaneously for the first time in several sites in north-eastern Spain, the Balearic Islands and southern France. A deep depression situated over the Atlantic at the time gave rise to warm south-westerly winds, accompanied by suspended dust, that blew towards the north-western Mediterranean Basin. Back trajectories of air masses at two different altitudinal levels indicate that the moths most probably originated from an area located in Morocco and northern Algeria, where C. ulceratalis can be extremely abundant. With winter approaching, this invasion of a typically non-migratory species into the north-western Mediterranean Basin provides a good example of the so-called "pied piper" phenomenon, by which wind-borne insects may be carried into areas unfavourable for survival or reproduction. However, because climate change may make the establishment of this and other African species more likely in the future, we suggest that monitoring of this process may become an essential issue in the coming years.